Aspectos da sustentabilidade nas explorações do milho em assentamentos rurais no centro oeste de Sergipe - Santana, Ana Paula Silva de (2019)
Corn is a crop of important economic interest for both in natura consumption and raw material production for the industry. The grain maize production in the agricultural monoculture system expanded in the Sergipe's territory and introduced changes and new technologies on the production way, as well as changes in the intensity of natural resources use. Thus, the insertion of the maize technological package has brought a series of social, economic and environmental impacts that express the importance of evaluating the sustainability of these agroecosystems. This evaluation would have as objective to observe the interrelationships between agricultural activity and the environment, plus the possibility of its long-term maintenance. The assessment of sustainability is based on the use of evaluation methods, which are mostly consisted of a set of indicators aimed at the organization, monitoring, and analysis of agricultural systems. At the international and national levels, different methods of sustainability assessment have been developed, whose proposal seeks to address different realities and types of existing agricultural systems. In France, it was developed a sustainability assessment method called Indicateurs de Durabilité des Exploitations Agricoles or Farm Sustainability Indicators (IDEA). The IDEA method is a tool that generates agricultural property diagnosis from the dimensions of agri-environmental, socio-territorial and economic sustainability. In Brazil, two methods have been highlighted in the assessment of sustainability in rural properties: Avaliação Ponderada de Impacto Ambiental de Atividades do Novo Rural or Weighted Assessment of Environmental Impact of New Rural Activities (APOIA Novo-Rural) and Indicadores de Sustentabilidade em Agroecossistemas or Agroecosystem Sustainability Indicators (ISA). Unlike the IDEA, APOIA Novo-Rural and ISA are methods that aim at creating a sustainability index (value) for rural properties. Agriculture is the segment of the production chain that most depends on environmental conditions. Thus, the greatest advantage of its sustainability assessment is to identify the potential impacts of this system and direct them for analysis and monitoring. This research aims to evaluate the sustainability in rural settlements of Agreste Sergipano mesoregion in Brazil, whose main economic activity focus on grain maize cultivation (Zea mays). The thesis is organized into four chapters. The first chapter discusses the process of agriculture modernization and its impasses in sustainability. The second chapter presents the comparative analysis of the IDEA, APOIA Novo-Rural, and ISA methods, by exposing their main characteristics and approaches to family farming systems. The third chapter analyzes the scenario of maize production in rural settlements, by using the IDEA method. Finally, the fourth chapter shows the influence of agribusiness political action and the irregular distribution of rainfall on the socioeconomic dynamics of rural settlements.